A Principal Components Analysis of the National Accounting Data of Eighteen OECD Countries - Oksanen, Ernest H.; Williams, James R. (The Review of Economics and Statistics, 1974)
Ernest H. Oksanen, James R. Williams, A Principal Components Analysis of the National Accounting Data of Eighteen OECD Countries, The Review of Economics and Statistics, Vol. 56, No. 4 (Nov., 1974), pp. 559-562